Survey of Opioid and Barbiturate Prescriptions in Patients Attending a Tertiary Care Headache Center. Issue 9 (28th August 2015) - Minen, Mia T.; Lindberg, Kate; Wells, Rebecca E.; Suzuki, Joji; Grudzen, Corita; Balcer, Laura; Loder, Elizabeth
<x xml:space="preserve">Abstract</x> Objective To educate physicians about appropriate acute migraine treatment guidelines by determining (1) where headache patients were first prescribed opioids and barbiturates, and (2) the characteristics of the patient population who had been prescribed opioids and barbiturates. Background Several specialty societies issued recommendations that caution against the indiscriminate use of opioids or barbiturate containing medications for the treatment of migraine. These medications are still being prescribed in various medical settings and could put headache specialists in a difficult position when patients request these agents. Methods Patients presenting to a headache center comprised of eight physicians were asked to complete a survey that assessed headache types, comorbid conditions, and whether they had ever been prescribed opioids or barbiturates. If they responded affirmatively to the latter question, they were asked about the prescribing doctor, medication effectiveness, and whether they were currently on the medication. Data collection took place over a one month period. Results Two hundred forty‐four patients were given the survey and 218 of these patients completed it. The predominant diagnosis was migraine (83.9%). More than half of the patients reported having been prescribed an opioid (54.8%) or a barbiturate (56.7%). About one fifth were on opioids (19.4%) or barbiturates (20.7%) at the time of completing the survey. Most patients reported being on opioids for more than 2 years (24.6%) or less than one week (32.1%). The reasons most frequently cited for stopping opioids were that the medications did not help (30.9%) or that they saw a new doctor who would not prescribe them (29.4%). Among patients who had previously been on barbiturates, 32.2% had been on these for over 2 years. Most patients (61.8%) stopped barbiturates because they did not find the medication helpful, while 17.6% said they saw a new doctor who would not prescribe them. The physician specialty most frequently cited as being the first prescriber for opioids was emergency medicine (20.2%) with family doctors and general neurologists the next groups at 17.7% each. General neurologists were the most frequent (37.8%) first prescribers of barbiturates. Conclusions Approximately 20% of patients presenting to a headache center reported current use of opioids and/or barbiturates. ED physicians were reported to be the most frequent first prescribers of opioids and general neurologists were the most frequent first prescribers of barbiturates. Taken as a whole, these data provide a useful snapshot of the wide variety of physician specialties that might benefit from additional education on the appropriate use of opioids and barbiturate‐containing medications in patients with headaches.